IMPLEMENTASI TEKNOLOGI MELALUI MYRISA UNTUK MENINGKATKAN EFEKTIVITAS PELAYANAN RSI SULTAN AGUNG BANJARBARU - Maliki, Muhammad Al; Sidiq, Abdurrahman; Marliadi, Reny; Hastuti, Eny; Hasymi, Liana Fitriani (LPPM Universitas Awal Bros, 2025)
The development of information technology has brought significant changes in various sectors, including health services. Online registration applications are one of the innovations that aim to improve the efficiency and effectiveness of services in hospitals. The purpose of this study was to analyze the effectiveness of the MyRisa online registration application in services at RSI Sultan Agung Banjarbaru. This study used a descriptive qualitative method with data collection techniques using the interview method with 8 informants, namely the head of IT, 2 registration officers and 5 patients using the MyRisa application. The results of the study showed that in terms of overall effectiveness, the implementation of the MyRisa application had been achieved in several important aspects of service at RSI Sultan Agung Banjarbaru. However, the hospital needs to make adjustments and improvements to these aspects to ensure that this application can be well received by all patients, especially those who have limitations in accessing or using technology. Keywords : Online Registration Application, Qualitative Analysis, Effectiveness